Theoretical Study on Low-Chirp Directly Modulated DFB Lasers with (110)-Oriented Quantum Well - Jianwei Li; Mengzhu Hu; Xinyang Su; Yanting Liu; Ke Zhan (Photonics)
The low-chirp operation of distributed feedback lasers is highly desirable in high-speed and high-bit rate optical transmission. In this article, we address this issue by theoretically investigating the possibility of further a reduction in the linewidth enhancement factor (LEF) of a quantum well (QW). The energy band structure of AlGaInAs quantum-well DFB lasers grown with a (110) crystal orientation in the active region of the L-band has been theoretically analyzed using multi-band k.p perturbation theory, by reducing the asymmetry of conduction bands and valence bands and thus the linewidth enhancement factor parameter, which is related to the frequency chirp. Simulation results show that the LEF of the directly modulated DFB laser is reduced from 2.434 to 1.408 by designing the (110)-oriented compression-strained Al0.06Ga0.24InAs multiple-quantum-well structure, and the eye diagram of the (110)-oriented quantum-well DFB laser with a digital signal transmission of 20 km is significantly better than the (001) crystal-oriented quantum-well DFB laser for the 10Gbps optical fiber communication system, thus achieving a longer distance and higher-quality optical signal transmission.